Why (and how to) trust Institutions? Hospitals, Schools, and liberal Trust - Pierre Lauret (Rivista di Estetica, 2018)
This is a paper about how we relate to institutions. Its aim is two-fold: accounting for what it is to ‘trust an institution’, and cashing out the right attitude to have towards public institutions. The descriptive account shows that ‘trusting institutions’ is a complex and ambivalent phenomenon, which oscillates between proper trust (as a two-place relation) and mere reliance, depending on the social function of the institution at hand. The normative proposal highlights the merit of a liberal form of trust in public institutions, as opposed to totalitarian and libertarian attitudes. To do this, the paper, reviewing a large set of public and private institutions, focuses on two cases, healthcare and educational institutions.